The optimum light wavelength and light intensity for production of African catfish, clarias gariepinus juveniles - Sallehudin, Muhammad Firdaus; Mukai, Yukinori (2015)
The objective of the present study was to find the optimum light condition for rearing of African catfish juveniles. For this purpose, juveniles of African catfish were reared under five light wavelengths (white, blue, green, yellow and red) with three light intensities (1.40x10-3, 1.40x10-2, and 1.40x100 µmoles/m²/s). The survival rates, specific growth rates and production indexes were calculated at the end of the experiments. The results of present study showed that yellow light wavelength with 1.40x100 µmoles/m²/s have the tendency of higher production indexes compared to other light conditions.